Vascular Decoupling in Septic Shock: The Combined Role of Autonomic Nervous System, Arterial Stiffness, and Peripheral Vascular Tone - Carrara, Marta; Herpain, Antoine; Baselli, Giuseppe; Ferrario, Manuela (Frontiers in Physiology, 2020)
Background Acute inflammation and sepsis are known to induce changes in vascular properties, leading to increased arterial stiffness; at the same time, the autonomic nervous system (ANS) also affects vascular properties by modulating the arterial smooth muscle tone, and it is widely reported that sepsis and septic shock severely impair ANS activity. Currently, clinical guidelines are mainly concerned to resuscitate septic shock patients from hypotension, hypovolemia, and hypoperfusion; however, if the current resuscitation maneuvers have a beneficial effect also on vascular properties and autonomic functionality is still unclear. The objective of this work is to assess the effects of standard resuscitation at vascular level and to verify if there is any association between alterations in vascular properties and ANS activity. Methods Six pigs underwent a protocol of polymicrobial septic shock and resuscitation (fluids and noradrenaline). The arterial blood pressure (ABP) waveform was recorded in the central aorta and in the peripheral radial and femoral artery. The characteristic arterial time constant was computed at the three arterial sites based on the two-element Windkessel model, to characterize the overall arterial vascular tree. Moreover, independent estimates of total arterial compliance (AC) and total peripheral resistance (TPR) were performed. Baroreflex sensitivity (BRS), low frequency (LF, 0.04–0.15 Hz) spectral power of diastolic blood pressure, and indices of heart rate variability (HRV) were computed to assess ANS functionality. Results Septic shock induced a severe vascular disarray, decoupling the usual pressure wave propagation from central to peripheral sites; this phenomenon appeared as an inversion of the physiological pulse pressure (PP) amplification, with a higher PP in the central aorta than in the peripheral arteries. The time constant was decreased, together with AC and TPR. ANS dysfunction was described by a reduced BRS, decreased LF power, and suppressed HRV. This compromised condition was not resolved by administration of fluids and noradrenaline. Thus, a persistent vascular and autonomic dysfunction were reported also in the resuscitated animals, and they were found to be significantly correlated. Conclusion Measures of vascular function and ANS activity could add information to standard hemodynamic and clinical markers, and the current resuscitation strategies could benefit from the adjunction of these additional functional indices.